Making Aromatherapy Candles from Patchouli Oil Extract (Pogostemon cablin Benth.) and Crude Glycerol from Used Cooking Oil: Pembuatan Lilin Aromaterapi dari Ekstrak Minyak Nilam (Pogostemon cablin Benth.) dan Crude Gliserol dari Minyak Jelantah - Muhammad Taufiq Thahir; Indira Fitriani (Unit Penelitian dan Pengabdian Kepada Masyarakat, AK-Manufaktur Bantaeng, 2023)
Used cooking oil is a compound with a carbon chain that is not quickly decomposing, so it will harm the environment. The effort that can use used cooking oil is to process it into a product with a selling value, namely aromatherapy candles. This study aims to determine the effect of adding crude glycerol and patchouli oil extract to produce long-lasting aromatherapy candles. Wax production in this study consisted of the transesterification of used cooking oil and the extraction of patchouli plants using the maceration method. Aromatherapy candles comprise 24 grams of stearic acid and 6 grams of paraffin. It added crude glycerol with variations of 1.5, 2.5, 3.5, and 4.5 grams. In each addition, variation crude glycerol added one drop and two drops of patchouli essential oil. This experiment's primary research is physical testing, including a melting point test, burning time test, flame test, and aroma test. The sample composition that produces wax with the longest burning time is adding 2.5 grams of crude glycerol and four drops of patchouli essential oil with a burn time of 6 hours and 8 minutes.